The role of the environment in entrepreneurial propensity of youngsters' business ideas - Katalin Czakó; Csilla Polster; Santi Setyaningsih; Tihana Vasic (Journal of Innovation and Entrepreneurship, 2023)
Entrepreneurship shows regional differences through countries' history, economic environments, society and habits of individuals. Youngsters can think globally and have the highest skills to access information and know-how. This paper collects data from students' project work from different countries and extract that information, which can give interesting input to describe regional effects on entrepreneurial propensity through a quantified semantic analysis. Youngsters from 12 countries received the same instructions to present their national economies and then create a business there. The fundamental question of the paper is that are there any definable attributes from the economic environment, which effect youngsters' entrepreneurial propensity? How can we describe these effects? We linked values and made a numerical evaluation of youngsters' business concepts, which gives not only a range but also the grade of the presence of local or regional elements. The results show that the more exact special elements of a national economy mentioned, the more barriers participants are aware of. The research concept and the results may give useful inputs in knowledge transfer and education of entrepreneurship.
Keywords: F64; L20; L26; 650; Entrepreneurial environment; Entrepreneurial propensity; Regional; Youngsters